Ukraine : Staff Report for the 2013 Article IV Consultation and First Post-Program Monitoring. (IMF Staff Country Reports; Country Report, 2014)
This paper discusses Ukraine's 2013 Article IV Consultation and First Post-Program Monitoring. The Ukrainian economy has been in recession since mid-2012, and the outlook remains challenging. In January-September 2013, GDP contracted by 1u percent year-over-year, reflecting lower demand for Ukrainian exports and falling investments. Consumer prices stayed flat, held down by decreasing food prices and tight monetary policy. The fiscal stance loosened in 2012-2013, contributing to the buildup of vulnerabilities. Ukraine remains current on all its payments to the IMF, and the authorities have reaffirmed their commitment to repay all outstanding IMF credit.